The Tragedy of a Region, the Tragedy of an Individual: A Review of Bogusław Tracz and Sebastian Rosenbaum’s Book Punkt zwrotny. Rozmowa o roku 1945 na Górnym Śląsku (Zaranie Śląskie, 2025)
A Review of Bogusław Tracz and Sebastian Rosenbaum’s Book Punkt zwrotny. Rozmowa o roku 1945 na Górnym Śląsku
Keywords: Upper Silesian tragedy; 1945; family history; historical memory; review